COMPARISON OF SOME BAYES' ESTIMATORS FOR THE WEIBULL RELIABILITY FUNCTION UNDER DIFFERENT LOSS FUNCTIONS - Rasheed, Huda.; Al-Baldawi, Tasnim; Al-Obedy, Nadia (Iraqi Journal of Science, 2024)
Weibull distribution is one of the most widely used distributions oflifetime in reliability engineering. It has the ability to provide reasonablyaccurate failure analysis and failure forecasts especially with extremelysmall samples. Bayesian approach has received a lot of attention alongwith the traditional methods of estimation such as maximum likelihoodand moment estimation methods. The object of the present paper is tocompare some Bayes' estimators for the scale Parameter of the Weibullreliability function using different loss functions, based on Jeffrey priorinformation for estimating the scale parameter of Weibull distribution.The comparison was based on a Monte Carlo study. Through thesimulation study comparison was made on the performance of theseestimators with respect to the mean square error (MSE) and the meanpercentage error (MPE). The results of comparison by MSE showedthat the Weibull reliability function based upon squared error lossfunction was the best followed by the modified El- Sayyad's lossfunction. While comparison by MPE showed the reverse.